Recent Trends and Long-standing Problems in Archaeological Remote Sensing. Issue 1 (10th May 2018) - Opitz, Rachel; Herrmann, Jason
The variety and sophistication of data sources, sensors, and platforms employed in archaeological remote sensing have increased significantly over the past decade. Projects incorporating data from UAV surveys, regional and research-driven lidar surveys, the uptake of hyperspectral imaging, the launch of high-temporal revisit satellites, the advent of multi-sensor rigs for geophysical survey, and increased use of structure from motion mean that more archaeologists are engaging with remote sensing than ever. These technological advances continue to drive research in the specialist community and provide reasons for optimism about future applications, but many social and technical obstacles to the integration of remote sensing into archaeological research and heritage management remain. This article addresses the challenges of contemporary archaeological remote sensing by briefly reviewing trends and then focusing on providing a critical overview of the main structural problems. The discussion here concentrates on topics that have dominated the discourse in recent archaeological literature and featured prominently in ongoing fieldwork for the past decade across three broad segments of landscape archaeology: data collection in the field, the current state of data access and archives, and processing and interpretation.